Promoting physical activity in rheumatoid arthritis: a narrative review of behaviour change theories. (4th December 2015) - Larkin, Louise; Kennedy, Norelee; Gallagher, Stephen
Abstract: Purpose : Despite physical activity having significant health benefits for people with rheumatoid arthritis (RA), current levels of physical activity in this population are suboptimal. Changing behaviour is challenging and interventions aimed at increasing physical activity in this context have had varying levels of success. This review provides an overview of common behaviour change theories used in interventions to promote physical activity and their application for promoting physical activity in people with RA. Method : A scoping, narrative review was conducted of English language literature, using the search terms "physical activity/exercise" and keywords, which are associated with behaviour change interventions. The theoretical basis of such interventions in people with RA was assessed using the "theory coding scheme". Results : Six theories which have been used in physical activity research are discussed. Further, four studies which aimed to increase physical activity levels in people with RA are explored in detail. Conclusions : To date, behaviour change interventions conducted in RA populations to increase physical activity levels have not had a strong theoretical underpinning. It is proposed that an intervention utilising the theory of planned behaviour is developed with the aim of increasing physical activity in people with RA. Implications for Rehabilitation: Interventions to promote physical activity in the rheumatoid arthritis (RA) population have failed to change participants' behaviour. A small number of studies have used behaviour change theories in the development and delivery of interventions. The theory of planned behaviour is recommended as the theoretical basis for an intervention to promote physical activity in the RA population.